Effect of sub-surface tillage and chemical fballow management on soil N-NO₃- disponibiloity and yield of no-till corn planted on grazed oats - Ernst, O.; Bentancur, O. (Agrociencia Uruguay, 2004)
Only 12% of the total corn area in Uruguay is planted under no tillage (NT) systems unlike other summer crops like sunflower or soybean. In Dairy production farms, corn is frequently planted after winter-grazed oats. Lower corn grain yields with NT have been attributed to implanation failures due to surface soil compaction. We studied the residual effect of paralowing to 0.4m depth (P-NT) vs regular NT as sub-superficial tillage during the spring previous to the corn crop, and its interaction woth a combination of days of oat regrowth and days between total herbicide application and corn planting, leaving the oat.stubble on the soil surface (15+50, 33+32, and 10+12). Treatment 33+32 also was evaluated removing the stublble (32+32-R). P-NT reduced soil strength between 0,1 and 0,4 depth, but not in the upper 0,1m. Soil N-NO3- concentration was increased (P=0,05) by the length of the chemical fallowing, showing no significant interaction with paraplowing. The amount of N-NO3- in the first 0,02m of soil profile was 13mg kg-1 with 15+50, and 5mg kg-1 with 10+12. NT without paraplowing determined a lower number of corn plants (45549 vs. 52292 pl.ha-1, respectively, for NT and P-NT), which resulted in lower grain yield (5015 vs. 6192 kg ha-1). The best corn grain yield was obtained with 33+32, being 15% and 25% greater than 10+12 with NT and P-NT, respectively.